Financial policies and the prevention of financial crises in emerging market economies - Mishkin, Frederic S., 1951- 1951- (Policy research working papers, 2001)
In recent years we have seen a growing number of banking and financial crises in emerging market countries, with great costs to their economies. But we now have a much better understanding of why these crises occur and a better idea how they can be prevented